2014
DOI: 10.1039/c4ra06630h
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal synthesis and visible light-driven photocatalytic degradation for tetracycline of Fe-doped SrTiO3

Abstract: In this paper, Fe-doped SrTiO3 (FSTO) photocatalysts were successfully prepared via a facile solvothermal method, and their photocatalytic activities for degrading tetracycline (TC) under visible light irradiation were examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…This results are in a good agreement with Li et al [57]. They synthesized Fe-doped SrTiO 3 photocatalysts and examined their photocatalytic activities for degrading tetracycline (TC) under visible light irradiation.…”
Section: Photocatalytic Activity In Phenol Decompositionsupporting
confidence: 91%
See 1 more Smart Citation
“…This results are in a good agreement with Li et al [57]. They synthesized Fe-doped SrTiO 3 photocatalysts and examined their photocatalytic activities for degrading tetracycline (TC) under visible light irradiation.…”
Section: Photocatalytic Activity In Phenol Decompositionsupporting
confidence: 91%
“…They synthesized Fe-doped SrTiO 3 photocatalysts and examined their photocatalytic activities for degrading tetracycline (TC) under visible light irradiation. Although, based on the ESR analyses, they confirmed the presence of Å OH and O 2 ÅÀ , they suggest that O 2 ÅÀ and h + are mainly responsible for photocatalytic degradation of TC, while Å OH plays a much weaker role [57].…”
Section: Photocatalytic Activity In Phenol Decompositionmentioning
confidence: 96%
“…, all the diffraction peaks observed at values of 22.8 , 32.2 , 40 , 46.5 , 58 , 68 and 77.2 of STO NCs (I) match that of the pure SrTiO 3 (JCPDS: 35-0734),7 and no other impurity peaks are detected. The pattern is also suitable for Cu 2 O (II) (JCPDS: 05-0667), 13 which implies high purity of the as-prepared samples by our experimental strategies.…”
mentioning
confidence: 68%
“…[1][2][3] Currently, photocatalytically active semiconductors with good prospects are TiO 2 , SrTiO 3 and ZnO due to their outstanding properties, including chemical stability, strong oxidizing activity, corrosion resistance, and nontoxicity. [7][8][9] Many studies, including experimental results and theoretical calculations, have demonstrated that the heterojunction formed by TiO 2 and modied metal oxides contributes to the efficient separation of photo-generated electron-hole pairs, which prolong the lifetime of excited electrons and holes. Therefore, for practical applications, many methods have been developed for SrTiO 3 modication: noble metal deposition, metal or nonmetal ion doping, sensitization with organic polymers, and coupling with the other semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the photocatalytic degradation of TC using TiO 2 , ZnO and SrTiO 3 photocatalysts have been conducted by several researchers. [7][8][9] However, their practical application is limited as these catalysts are responsive under UV-light, which occupies only 4-5% of solar light. It is essential to explore novel photocatalyst with high degradation efficiency for TC under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%